Understanding e-carceration: electronic monitoring, the surveillance state, and the future of mass incarceration - Kilgore, James (The New Press, 2022)
Part one. Introducing e-carceration -- Part two. Connecting the dots: from ankle shackle to surveillance state -- Part three. Abolition and e-carceration.